Compliance To Iron Supplementation Among Pregnant Women: A Cross Sectional Study in Urban Slum - Dutta, Alpanarani J; Patel, Prakash; Bansal, R K (National Journal of Community Medicine, 2014)
Background: Noncompliance to the iron-folic acid tablets is one of the most important challenging factors in combating anaemia. The study was conducted to assess compliance to Iron folic acid supplementation in pregnancy and to study the factors affecting it. Methods: The study included 239 pregnant women of gestational age 4th to 6th months from anganwadis of Surat Municipal Corporation area. Data was collected by personal interview with prestructured questionnaire. The data was analyzed using epi info software. Results: The results show that compliance to iron pills is increases with increase in level of education, early registration, increase in number of antenatal visits and knowledge of haemoglobin status and iron pill dose. Women from nuclear family with less number of children have better compliance. The overall compliance was found to be 61.7%. Forgetfulness, ignorance toward self-health care and to visit health facility, big size of tablets and palatability, and frustration to take daily pills appears to main causes of non-compliance. Conclusion: Every six out of ten pregnant women were found taking iron supplement pills. As number of antenatal visits and knowledge of dose and duration of iron supplementation pills are independently affecting compliance to iron pills, increasing number of antenatal visits and imparting knowledge about dose and duration of iron supplementation pills will improve compliance to iron pills.